(untitled) (Law Research Review Quarterly, 2025)
This research investigates the absence of constitutional protection for freelance workers, particularly freelance models, within Indonesia’s labor law framework. While the Constitution of the Republic of Indonesia guarantees the right to work and to fair and decent remuneration, these protections are primarily structured around formal employment relationships, thereby excluding a growing segment of the labor force that operates within non-standard, flexible arrangements. The study aims to analyze the extent to which the current legal system, particularly Law No. 13 of 2003 on Manpower, as amended by Law No. 6 of 2023 on Job Creation accommodates or neglects freelance workers in terms of legal recognition, job security, and social protections. Using a normative juridical method with a statute and conceptual approach, this research draws from doctrinal legal analysis to critically evaluate the legal construction of employment relationships. The findings reveal significant normative gaps that leave freelance models vulnerable to exploitation, lacking access to written employment contracts, social security, and fair dispute resolution mechanisms. The study proposes a reconfiguration of legal norms to introduce a Constitutional Employment Contract model, which accounts for the flexible nature of freelance work while ensuring fundamental labor rights. Additionally, the paper recommends the establishment of an independent regulatory body to provide legal oversight and advocacy for flexible workers. Ultimately, this research concludes that achieving social justice for all workers in the modern labor market necessitates a transformation of Indonesia’s labor law regime toward a more inclusive and responsive constitutional framework.